5hmC-profiles in Puerto Rican Hispanic/Latino men with aggressive prostate cancer - Patel, Manishkumar S.; Almubarak, Mousa; Matta, Jaime; Ortiz-Sanchez, Carmen; Encarnacion, Jarline; Ruiz-Deya, Gilberto; Dutil, Julie; Dhillon, Jasreman; Yamoah, Kosj; Berglund, Anders; Park, Hyun; Kilari, Deepak; et al. (Frontiers in Oncology, 2025)
IntroductionPuerto Rican (PR) Hispanic/Latino (H/L) men are an understudied population that has the highest prostate cancer (PCa) specific mortality among other Hispanic populations. Little information is known about the higher mortality in PR H/L men. It is thought that epigenetic changes in key genes may play a critical role in aggressive tumors.MethodsWe aimed to identify key 5-hydroxymethylcytosine (5hmC) changes in PR H/L men with aggressive PCa. We performed sequencing analysis using the 5hmC-enriched DNA from 22 prostate tumors and 24 adjacent normal FFPE samples.ResultsWe identified 808 differentially methylated genes (DMGs) in tumors compared to adjacent normal tissues. These genes suggest key mechanisms, including upregulated signatures of negative Androgen Receptor (AR) regulation, Wnt/β-catenin pathway activation, and downregulation of tumor suppressor genes. Pathway analysis of DMGs demonstrated that DNA repair pathway was most upregulated in tumors. Since 5hmC abundance positively correlates with gene expression levels, we further investigated 808 DMGs in TCGA PCa gene expression data. Further, we identified 59 DMGs with significant gene expression changes in the same direction. Additionally, we identified 111 aggressiveness-related DMGs, of which, two hypomethylated genes (CCDC122, NUDT15) and four hypermethylated genes (PVT1, RPL30, TRMT12, UBR5) were found to be altered at transcriptomic level in a concordant manner in PR H/L PCa patients. Aberrant 5hmC and GE changes in these six genes were also associated with progression-free survival in the mixed PCa population.DiscussionThe 5hmC modifications and associated gene expression changes in these six genes could be linked to the highest prostate cancer (PCa)-specific mortality in PR H/L men. In conclusion, our study identified 59 DMGs showing concordant epigenetic and transcriptomic changes in tumor tissues and 111 DMGs showing association with aggressive PCa among PR H/L men. Our findings have significant implications for understanding these key genes’ molecular mechanisms, which may drive PCa progression and mortality in this population. This will help in developing potential biomarkers or therapeutic targets for personalized treatment strategies in this high-risk subgroup. Future research will explore how these genes contribute to PCa-specific mortality through molecular analyses, with plans to validate them in a larger validation cohort.